Research on vector-borne diseases: implementation of research communication strategies - Thomas Scalway; Mariam Otmani del Barrio; Bernadette Ramirez (BMC, 2019)
Abstract Background Effective communication of research findings on vector-borne diseases in Africa is challenging for a number of reasons. Following the experiences of a number of researchers over the life of a project, this article looks for lessons that can be shared with the wider research community. Main body Between 2014 and 2017, a set of five inter-disciplinary teams from seven African countries collaborated on a project focusing on vector-borne diseases in the context of climate change. A central objective of this work was to influence policy and programming with relevant research findings. This article examines how principles of research communication, derived from the literature and current guidelines, can be applied in practice. Several challenges and lessons are highlighted, showing that research communication takes place within difficult constraints and in complex, fluid institutional and political environments. The processes of communication between policymakers and researchers including stakeholder mapping, defining research communication plans and tailoring communication products are discussed. Conclusions The article concludes that while guidelines and frameworks for research communication are helpful, they should not detract from the ability of local teams to adapt to circumstances. Of key importance are the relationships and networks of local research teams.